Environmental, psychological, and social influences on physical activity among Japanese adults: structural equation modeling analysis - Ishii, Kaori (BioMed Central, 2010)
BACKGROUND: An understanding of the contributing factors to be considered when examining how individuals engage in physical activity is important for promoting population-based physical activity. The environment influences long-term effects on population-based health behaviors. Personal variables, such as self-efficacy and social support, can act as mediators of the predictive relationship between the environment and physical activity. The present study examines the direct and indirect effects of environmental, psychological, and social factors on walking, moderate-intensity activity excluding walking, and vigorous-intensity activity among Japanese adults. METHODS: The participants included 1,928 Japanese adults aged 20-79 years. Seven sociodemographic attributes (e.g., gender, age, education level, employment status), psychological variables (self-efficacy, pros, and cons), social variables (social support), environmental variables (home fitness equipment, access to facilities, neighborhood safety, aesthetic sensibilities, and frequency of observing others exercising), and the International Physical Activity Questionnaire were assessed via an Internet-based survey. Structural equation modeling was conducted to determine associations between environmental, psychological, and social factors with physical activity. RESULTS: Environmental factors could be seen to have indirect effects on physical activity through their influence on psychological and social variables such as self-efficacy, pros and cons, and social support. The strongest indirect effects could be observed by examining the consequences of environmental factors on physical activity through cons to self-efficacy. The total effects of environmental factors on physical activity were 0.02 on walking, 0.02 on moderate-intensity activity excluding walking, and 0.05 on vigorous-intensity activity. CONCLUSIONS: The present study indicates that environmental factors had indirect effects on walking, moderate-intensity activity excluding walking and vigorous-intensity activity among Japanese adults, especially through the effects on these factors of self-efficacy, social support, and pros and cons. The findings of the present study imply that intervention strategies to promote more engagement in physical activity for population-based health promotion may be necessary.